The Acceptance Level of The Role of Robots in Workplaces and Homes During The COVID-19 Pandemic - Research Proposal - Zuzanna BORDA; Jacek WINIARSKI (Communications of International Proceedings, 2021)
Robotization has always evoked extreme emotions - from a fascination with modernity to its rejection as an expression of fear arising from the possibility of replacing human activities with robotic work. In the spring of 2020, the world was overwhelmed by the crisis resulting from the spread of the COVID-19 pandemic. The importance of robotization has been significantly strengthened. The use of robots replacing human labor significantly influenced the reduction of the process of spreading the coronavirus SARS-CoV-2. The question arises - what is the current attitude of people to the processes of robotization? The aim of this article is to present a proposal for research (emerging research) on the level of acceptability of the use of robots in professional work as well as in-home applications. Objective assessment can be obtained by using technology acceptance models. Among the set of models developed in science and verified in practice, the Unified Theory of Acceptance and Use of Technology (UTAUT) model deserves special attention because of its flexibility and high predictive power. In the described research we plan to use an enriched UTAUT model, adding three new variables to the original version: Mental Influence, Robot Superiority, and Complexity of Usage. We hope that the results of the planned research will make it possible to formulate recommendations for actions aimed at reducing civilizational exclusion (e.g. digital exclusion) and reducing the emotional and intellectual distance between generations and cultures.
Keywords: robotization; unemployment; COVID-19 pandemic